2020
DOI: 10.1242/dmm.042689
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models of sarcopenia

Abstract: Sarcopeniathe accelerated age-related loss of muscle mass and functionis an under-diagnosed condition, and is central to deteriorating mobility, disability and frailty in older age. There is a lack of treatment options for older adults at risk of sarcopenia. Although sarcopenia's pathogenesis is multifactorial, its major phenotypesmuscle mass and muscle strengthare highly heritable. Several genome-wide association studies of musclerelated traits were published recently, providing dozens of candidate genes, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 141 publications
3
35
0
Order By: Relevance
“…Zebrafish were presented as an aging model in 2002 by Gerhard et al who investigated the process of zebrafish aging and later demonstrated that it is comparable to human aging and suitable to study age‐dependent changes in musculoskeletal function (Gerhard, 2003; Gerhard & Cheng, 2002; Gerhard et al, 2002). Zebrafish as a model for aging has also been supported by the work of Kishi et al (Kishi, 2004; Kishi et al, 2003) The ease of care, prolific breeding, easy genetic manipulability, and ability to readily absorb drugs through their water make the zebrafish an attractive model to work with (Daya, Donaka, & Karasik, 2020; Maves, 2014; Volpatti et al, 2020). Additionally, zebrafish skeletal muscle makes up a large portion of the fish trunk and has a high degree of similarity with human muscle, including the presence of satellite‐like cells for muscle repair and regeneration (Gurevich et al, 2016; Hollway et al, 2007).…”
Section: Zebrafishmentioning
confidence: 98%
See 1 more Smart Citation
“…Zebrafish were presented as an aging model in 2002 by Gerhard et al who investigated the process of zebrafish aging and later demonstrated that it is comparable to human aging and suitable to study age‐dependent changes in musculoskeletal function (Gerhard, 2003; Gerhard & Cheng, 2002; Gerhard et al, 2002). Zebrafish as a model for aging has also been supported by the work of Kishi et al (Kishi, 2004; Kishi et al, 2003) The ease of care, prolific breeding, easy genetic manipulability, and ability to readily absorb drugs through their water make the zebrafish an attractive model to work with (Daya, Donaka, & Karasik, 2020; Maves, 2014; Volpatti et al, 2020). Additionally, zebrafish skeletal muscle makes up a large portion of the fish trunk and has a high degree of similarity with human muscle, including the presence of satellite‐like cells for muscle repair and regeneration (Gurevich et al, 2016; Hollway et al, 2007).…”
Section: Zebrafishmentioning
confidence: 98%
“…Zebrafish were presented as an aging model in 2002 by Gerhard et al who investigated the process of zebrafish aging and later demonstrated that it is comparable to human aging and suitable to study age-dependent changes in musculoskeletal function (Gerhard, 2003;. Zebrafish as a model for aging has also been supported by the work of Kishi et al (Kishi, 2004;Kishi et al, 2003) The ease of care, prolific breeding, easy genetic manipulability, and ability to readily absorb drugs through their water make the zebrafish an attractive model to work with (Daya, Donaka, & Karasik, 2020;Maves, 2014;Volpatti et al, 2020).…”
Section: The Modelmentioning
confidence: 99%
“…Widely employed in developmental studies, the zebrafish is increasingly used in aging research, due to its relative short life-span (2–3 years), and based on the evidence that it shows hallmarks of gradual senescence, such as spinal curvature, muscle degeneration, and reduced physical ability [ 90 , 91 , 92 ]. Interestingly, recent research shows that zebrafish can be exploited for the investigation of neurodegenerative pathologies as Alzheimer disease, Parkinson disease [ 93 ], but also osteoporosis, sarcopenia [ 94 ], and age-dependent trainability [ 95 ].…”
Section: Fishesmentioning
confidence: 99%
“…To treat muscle wasting diseases such as sarcopenia, researchers extensively studied the functions and structural properties of MSTN (encoded by the MSTN gene). MSTN is the most studied member of the TGF-β family and a negative regulator of skeletal muscle growth and development [ 54 ]. Another study suggested that the amount of PR domain-containing 16 (PRDM16) gene could regulate brown adipose tissue, white adipose tissue, and muscle cell metabolism [ 55 ].…”
Section: Risk Factors For Sarcopeniamentioning
confidence: 99%